IMPLEMENTING DIGITAL COMPETENCE FRAMEWORK FOR FUTURE TEACHERS’ PROFESSIONAL DEVELOPMENT - Beskorsa, Olena (Професіоналізм педагога: теоретичні й методичні аспекти, 2018)
The mass implementation of digital technology in professional activity and everyday life causes increasing demands for training future teachers who are responsible for preparing the young generation to participate efficiently in modern society. Thus, the article reveals the relevant issue of future teachers’ professional development through implementing digital competence framework. The development of teachers’ digital competence is a target of a number of foreign and Ukrainian researchers. The theoretical determination of the concept “digital competence” and “digital literacy” are represented in works by D. Belshaw, P. Gilster, N. Hockly, N. Sonck, S. Livingstone, E. Kuiper and others. Terminological clarification of these concepts are highlighted in the researches of Ukrainian scientists (V. Bykov, L. Havrilova, O. Danylchuk, M. Zhaldak, A. Kolomiiets, O. Sysoieva, I. Smyrnov, O. Spirin and others). The purpose of the paper is to present the theoretical justification of the digital competence framework for future teachers and in such a way to contribute to their professional development. In this paper, the author proves that digital competence is a constituent part of professional competence. The structure of digital competence is characterized and visualized. It contains the following elements: ICT fluency; data, information and media literacy; digital self-development; communication, networking, participating; digital innovation and creation. The detailed analysis of European Framework for Digital Competence of Educators shows the elements of the competence, such as professional engagement, digital resources, teaching and learning, assessment, empowering learners, and facilitating learners’ digital competence. The author emphasizes on the necessity to include the following element to the framework: motivation and positive self-perception, new methodologies for digital competence development. As they are essentioal for implementing digital technologies in educational process, as well as allows to establish indicators for evaluating the level of its development. It is concluded that regarding to the different aspects of future teachers’ digital competence, which we have expounded on in this paper, clearly reflects all the demands, which should be taken into consideration, while designing digital competence framework for educators in Ukraine according to educational reforming and upgrading process, as well as the relationship that must be established between the major components of teachers’ digital competence.